Developing a Customer Service Communication Model to Enhance Professional Image: A Case Study of Early-Stage Laundry Business - Sondang Beatrix Siahaan; Novi Handayani Simbolon; Fatma Dwi Jati; Khanti Listya (Institute of Computer Science (IOCS), 2026)
While early-stage service business often struggle with brand perception, research on standardized communication frameworks for MSME remains limited. This study develops a customer service communication model designed to bridge the gap between operational service and professional image in early-stage laundry businesses. Utilizing the systematic ADDIE (Analysis, Design, Development, Implementation, and Evaluation) framework, this research employs a comprehensive R&D (research and development) approach to ensure the model is both theoretically sound and practically viable. Grounded in the Osgood-Schramm circular communication theory, this research adopts a a qualitative developmental approach. Through semi-structured interviews, field observation, and data triangulation, this study identifies critical touchpoints in the service communication cycle. The result is a synchronized communication flow and a standardized pocketbook guide tailored for three pivotal interactions: customer drop-off, pick-up, and complaint handling. Beyond its practical utility, this research contributes to service communication literature by operationalizing theoretical models into actionable frameworks for informal business sectors. The findings demonstrate that a structured developmental approach to interpersonal communication serves as a vital catalyst for enhancing service quality and fostering long-term business resilience